The year in cardiology: acute coronary syndromes - Banning, Adrian P.; Crea, Filippo; Lüscher, Thomas F. (SA Heart Journal, 2020)
There is an unmet need in the management of acute coronary syndromes (ACS). In 2019, there were a number of important papers published in the European Heart Journal and other journals that deepened our knowledge of the spectrum of ACS and their management.